1990
DOI: 10.1037/0278-7393.16.1.98
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination learning during the first year: Stimulus and positional cues.

Abstract: In four studies, 3-, 6-, and 9-month-old human infants were tested in a discrimination learning task in which visual fixation to a particular stimulus or lateral position was reinforced with an auditory stimulus. In Experiment 1, all age groups exhibited acquisition, extinction, and reinstatement of fixation to the reinforced target or position. Experiment 2 revealed that 3-month-olds retained the positional discrimination but not the stimulus discrimination after a 5-min delay between acquisition and extincti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 38 publications
3
12
0
Order By: Relevance
“…At the individual level, however, looking and memory formation have been reported to undergo nonlinear transitions across learning. Roder, Bushnell, and Sasseville (2000; see also Colombo, Mitchell, Coldren, & Atwater, 1990) found that infants transition from exhibiting a familiarity preference to exhibiting a novelty preference as quickly as from one trial to the next. Infants rarely exhibited a null preference in between, a signature of linearly transitioning from encoding to memory.…”
Section: Setting the Stage For A New Theorymentioning
confidence: 95%
“…At the individual level, however, looking and memory formation have been reported to undergo nonlinear transitions across learning. Roder, Bushnell, and Sasseville (2000; see also Colombo, Mitchell, Coldren, & Atwater, 1990) found that infants transition from exhibiting a familiarity preference to exhibiting a novelty preference as quickly as from one trial to the next. Infants rarely exhibited a null preference in between, a signature of linearly transitioning from encoding to memory.…”
Section: Setting the Stage For A New Theorymentioning
confidence: 95%
“…Microstructure variation in posterior aspects of the ventral visual pathway was associated with the speed at which the infant is able to process and encode information about the stimulus (Colombo & Mitchell 2009). A shorter look duration is thought to reflect faster acquisition of information about the habituated stimulus, whereas a longer look duration may be the most valid and reliable aspect of habituation with regard to both individual and developmental differences (Colombo et al 1990). Moreover, FA values in the memory circuitry, including fornix, hippocampus, parahippocampus, and inferior temporal gyrus, predicted the performance of novelty preference in infants at 6 months of age.…”
Section: Diffusion Tensor Imaging Applications In Infant Researchmentioning
confidence: 99%
“…The NBAS yields measures of state, arousal, physiological reactivity and fundamental forms of attention [9], and has been shown to be a modest predictor of developmental status across the short term [10,11]. More importantly, the scale has shown on numerous occasions to be a sensitive outcome variable for aspects of infant risk and status [12]. In addition, two studies found the NBAS to be sensitive to both prenatal [13] and postnatal [14] nutritional status.…”
Section: Introductionmentioning
confidence: 99%